2015
DOI: 10.1155/2015/795435
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects and Mode of Action of Selected Essential Oils Components againstEscherichia coliandStaphylococcus aureus

Abstract: Bacterial resistance has been increasingly reported worldwide and is one of the major causes of failure in the treatment of infectious diseases. Natural-based products, including plant secondary metabolites (phytochemicals), may be used to surpass or reduce this problem. The objective of this study was to determine the antibacterial effect and mode of action of selected essential oils (EOs) components: carveol, carvone, citronellol, and citronellal, against Escherichia coli and Staphylococcus aureus. The minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
195
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(207 citation statements)
references
References 64 publications
(73 reference statements)
8
195
0
4
Order By: Relevance
“…Peptidoglycan layer damage and cell wall leakage caused by several medicinal plants active compounds leading to morphological changes on gram positive pathogenic bacteria were reported previously. [43][44] In this study, we also observed the significant morphological alteration on the cell growth of S. mutans and S. sanguis in DLBS1355 o/w emulsionsupplemented BHIB compared to untreated cells (Fig. 3).…”
Section: Discussionsupporting
confidence: 60%
“…Peptidoglycan layer damage and cell wall leakage caused by several medicinal plants active compounds leading to morphological changes on gram positive pathogenic bacteria were reported previously. [43][44] In this study, we also observed the significant morphological alteration on the cell growth of S. mutans and S. sanguis in DLBS1355 o/w emulsionsupplemented BHIB compared to untreated cells (Fig. 3).…”
Section: Discussionsupporting
confidence: 60%
“…By substituting the values of the above parameters into equation (2) [20,21] were also obtained using the dialysis method and therefore comparisons of the present with the previous data can be made. due to their accepted safe status [1][2][3][4]. Essential oils derived from aromatic plants and, oregano EO in particular fall into a group of antimicrobials that has attracted major attention as shown by the numerous reports in the literature [26][27].…”
Section: In Vitro Release Of Oregano Eomentioning
confidence: 99%
“…Selected oils have been shown to act on microbial cell surface causing disruption of the cell wall and the cytoplasmic membrane leading to lysis and leakage of intracellular compounds [1]. Because of the increasing problem of bacterial resistance to several antibiotics and their accepted safety profile, essential oils may be interesting candidates against microbial infections [2].…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EOs) and other secondary plant metabolites have been shown to possess strong antimicrobial effects against a range of foodborne pathogens such as Escherichia coli O157:H7, Listeria monocytogenes, Staphylococcus aureus, Bacillus cereus and Salmonella Typhimurium (Burt, 2004;Calo et al, 2015;Scollard et al, 2013). EOs and their components are hydrophobic, and it is believed that this enables them to dissolve in the lipids of the bacterial cell membrane and mitochondria, rendering them more permeable and leading to the leakage of essential cell content (Burt, 2004;Lopez-Romero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%